From ‘Persahabatan’ to ‘Friendship’: Exploring Translating Equivalence in Ika Ayu Rahmawati’s Whattpad Short Story - Shafara Dhuha 'Afanirazahra; Indriyati Hadiningrum; Rosdiana Puspita Sari (Jurnal Vokasia, 2023)
This article is entitled Translating “Persahabatan” from Indonesian Into English (A Wattpad Short Story by Ika Ayu Rahmawati). The “Persahabatan” short story is a teen fiction story published on the Wattpad app in 2020. This short story has been read by more than 24,000 users and voted about 301 times. The purposes of translating “Persahabatan” short story into English are to translate it from Indonesian into English, explain the process and the technique in the translation, and describe the difficulties and giving the solutions in the translation. This Wattpad short story is interesting to be translated in order to be found by Wattpad users from other countries and increase readers globally.